PENERAPAN SISTEM INFORMASI KEUANGAN PADA PERUSAHAAN PT PLN DAN PT TELKOM INDONESIA - Gunardi, Gunardi; Ismawati, Linna; Ibrahim, Muhammad; Anggareni, Kumala Fitria; Pengestu, Bagus; Marliyanti, Resti; Zahro, Fatimah (Universitas Kuningan, 2025)
In the era of technology, financial information systems have become a vital element for companies across various sectors, including PT PLN and PT Telkom Indonesia. This article aims to compare the implementation of financial information systems in these two companies while addressing the challenges and proposed solutions. Using a qualitative method with a descriptive, verificative approach and literature studies, it was found that PT PLN focuses more on centralized control and cashless transactions to ensure security and efficiency in customer interactions. In contrast, PT Telkom prioritizes detailed recording and internal cash management to improve accuracy and operational effectiveness. Challenges in implementation include human error, data breaches, complex user interfaces, and the risk of virus infections. Proposed solutions include employee training, access restrictions, user interface socialization, and strengthening digital security to ensure the system's sustainability and effectiveness